Nature of Enthusiasm - Rappaport, Alexander (project baikal, 2015)
Art and architecture of the avant-guard in the beginning of 20 century supposed to be connected with the general upheaval in cultural and spiritual life. But phenomenon of creative enthusiasm cannot be fully explained in terms of political and cultural events. Moving forces of that historical moment are still unexplained. It is supposed that such creative outburst could be regarded in the context of spiritual and religious practice as a hidden resurrection of irrational attitudes of cult.